Annual Conference "Development and Registration of Biotechnological Drugs" will be Held on June 17 in Moscow - article Editorial (Разработка и регистрация лекарственных средств)
We will talk about biotechnological drugs' life cycle, certain aspects of biotechnological drugs' development, research and production.